2017
DOI: 10.1038/s41598-017-13592-w
|View full text |Cite
|
Sign up to set email alerts
|

Immunoproteasome subunit ß5i/LMP7-deficiency in atherosclerosis

Abstract: Management of protein homeostasis by the ubiquitin-proteasome system is critical for atherosclerosis development. Recent studies showed controversial results on the role of immunoproteasome (IP) subunit β5i/LMP7 in maintenance of protein homeostasis under cytokine induced oxidative stress. The present study aimed to investigate the effect of β5i/LMP7-deficiency on the initiation and progression of atherosclerosis as a chronic inflammatory, immune cell driven disease. LDLR−/−LMP7−/− and LDLR−/− mice were fed a … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

5
8
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 34 publications
5
8
1
Order By: Relevance
“…Here, the results presented showed that β5i was upregulated in the atherosclerotic plaques of eKO mice (Figure ); genetic ablation or inhibition of β5i reduced lesional accumulation of apoptotic cells but enhanced MERTK‐mediated efferocytosis, therefore inhibited necrotic core formation and atherosclerosis progression (Figures ). However, our results are inconsistent with a recent study that showed that β5i deficiency had no significant effect on the initiation and progression of atherosclerosis in the LDL receptor KO mice fed with ATD . This is not the first time that gene function studies carried out in these two mouse models have yielded totally different results.…”
Section: Discussioncontrasting
confidence: 99%
“…Here, the results presented showed that β5i was upregulated in the atherosclerotic plaques of eKO mice (Figure ); genetic ablation or inhibition of β5i reduced lesional accumulation of apoptotic cells but enhanced MERTK‐mediated efferocytosis, therefore inhibited necrotic core formation and atherosclerosis progression (Figures ). However, our results are inconsistent with a recent study that showed that β5i deficiency had no significant effect on the initiation and progression of atherosclerosis in the LDL receptor KO mice fed with ATD . This is not the first time that gene function studies carried out in these two mouse models have yielded totally different results.…”
Section: Discussioncontrasting
confidence: 99%
“…It is noteworthy that deletion of both PSMB8 and PSMB10 subunits was required to decrease mTEC cellularity ( Figure 2F). Hence, consistent with a recent report (Hewing et al, 2017), the single deletion of PSMB8 (LMP7) appears insufficient to cause proteotoxic stress. Additionally, using in vivo approaches (i.e., thymus transplantation and systemic poly(I:C) administration), we showed that IP deficiency has a dramatic impact on the regenerative potential of mTECs.…”
Section: Discussionsupporting
confidence: 91%
“…Notably, the β5i/LMP7 subunit but not the β5 constitutive subunit was up-regulated in an in vitro and an in vivo model of pancreatitis. Increased β5 protein levels in acini from β5i/LMP7-deficient mice were observed as a compensatory mechanism, as seen before in other cell types (4647). However, from the data obtained in this study, the immunoproteasome represents the major proteasome type involved in a rapid and efficient response to inflammation and ER stress during pancreatitis.…”
Section: Discussionsupporting
confidence: 76%
“…The UPR encircles stress response signaling pathways triggered by accumulation of misfolded or damaged proteins in the ER lumen (57). Although some studies did not report differences in the capacities of the constitutiveand the immunoproteasome to degrade ubiquitinated protein targets (47,58), our work supports an essential role of the immunoproteasome in regulating this process and synchronizing UPR activation in pancreatitis. Unbalanced UPR, due to proteasome dysfunction has been implicated in the innate immune response, with the immunoproteasome playing a central role in the regulation of inflammation and UPR.…”
Section: Discussionsupporting
confidence: 57%